False Consciousness In Body Positivity Campaigns In Women's Lifestyle Media - Fadhil, Ahmad Raihan; Humeira, Bintan; Kurniawan, Rizaludin (Faculty of Da'wa and Communications Sciences, 2023)
This article aims to discover how women’s lifestyle media constructs a false awareness about women’s bodies through body positivity discourse. Using media and gender perspectives, false consciousness, body positivity, and Roland Barthes’ semiotic analysis, this research finds that the media produces body positivity discourse as a narrative that ‘all bodies are beautiful, whatever their shape.’ Body positivity discourse refers to fat bodies as ‘normality’ to fight the stigma that fat bodies are not beautiful and are a problem for women. Body positivity evolved from the fat acceptance movement. This body positivity discourse is built on the construct that women must accept their body shape to live happily. The media produces the message through photos and texts that fat bodies are delicate as long as they are healthy. It ignores that medical obesity carries serious health consequences for many women. Thus, this research shows that instead of building women’s positive acceptance of their body shape, the media creates a misguided consciousness of fat bodies from a medical perspective.